Analysis of the Objectives, Benefits, and Functions of Accreditation in Improving the Quality of Indonesia’s National School System Based on Standards - Arif Wahyudi; Ibnul Amin; Husnul Yaqin; Hilmi Mizani (PT Barkah Ilmi Fiddunya, 2026)
This study aims to comprehensively analyze the objectives, benefits, and functions of accreditation in improving the quality of Indonesia’s national school system based on established standards. It focuses on how accreditation operates as an external quality assurance mechanism that is both evaluative and transformative in fostering continuous improvement within educational institutions. The study employs a qualitative library research method, analyzing recent scholarly sources, including national and international journal articles, academic books, and relevant policy documents. Data are examined using content analysis to identify patterns, themes, and conceptual relationships related to accreditation and educational quality. The findings reveal that accreditation serves three primary roles: quality assurance, performance evaluation, and public accountability. It ensures the fulfillment of National Education Standards, improves teaching and learning quality, enhances teacher professionalism, and strengthens school management effectiveness. Functionally, it acts as an external quality control system that promotes transparency and public trust. The study also finds that its effectiveness depends on schools’ follow-up actions after evaluation. Its novelty lies in integrating the objectives, benefits, and functions of accreditation into a unified standards-based framework, highlighting its role as a transformative system grounded in continuous improvement, institutional reflection, and innovation